Improving the Quality of Solutions by Automated Database Design Systems with the Provision of Real World Knowledge - An Evaluation - Naoh, Shahrul Azman; Williams, Michael (Universiti Putra Malaysia Press, 2004)
Automated database design systems have the capability of assisting human designers in the process of database analysis and design. However, the capacity of these systems to produce quality solutions which are similar to expert human designers remains largely unresolved. Therefore, in recent years there have been a number of attempts to develop systems that are not only "knowledgeable" about database design process but also have the capability of exploiting knowledge of the real world. Although such use of real world knowledge was claimed capable of increasing the quality of design models, there is currently little, if any, formal evaluation that this claim has taken place. This paper presents such an evaluation of three existing approaches proposed to facilitate system-storage and exploitation of real world knowledge; the dictionary approach, the thesaurus approach, and the knowledge reconciliation approach. Results obtained have indicated that some of the approaches under examination in this study are capable of producing higher quality design models compared to when no such knowledge is in use. However, the ability of such representations of real world knowledge to achieve the standard quality of human generated design models remains unanswered.